"Anatomic" Single-Bundle Anterior Cruciate Ligament Reconstruction Reduces Both Anterior Translation and Internal Rotation During the Pivot Shift. (December 2014) - Porter, Mark D.; Shadbolt, Bruce
Background: The ability of single-bundle anterior cruciate ligament (ACL) reconstruction to restore rotational control has been questioned by proponents of the double-bundle technique. The term anatomic positioning has become popularized in recognition of the incorrect positioning sometimes used in the past, which may have contributed to the lack of rotation control. The pivot-shift test remains the most clinically useful measure of ACL deficiency, and it is now possible to measure it both accurately and objectively using computer navigation. Hypothesis: Single-bundle ACL reconstruction will reduce anterior translation and internal rotation of the tibia during the pivot-shift test when compared with the contralateral uninjured knee. Study Design: Descriptive laboratory study. Methods: A total of 20 patients with an acute isolated ACL rupture underwent reconstruction with a single-bundle autologous hamstring graft. Computer navigation was used intraoperatively to plot the pivot shift before and after reconstruction. The opposite uninjured knee was used as a control. Statistical analysis was used to compare the pivot shifts before and after surgery. Results: Single-bundle ACL reconstruction produced a significant reduction in anterior translation, from a mean ± SD of 17.4 ± 3.80 mm to 6.4 ± 1.95 mm ( P < .001), as well as in internal rotation, from 22.9° ± 5.91° to 7.5° ± 2.96° ( P < .001). The anterior translation in the reconstructed knees was similar to the control knees, 6.4 ± 1.95 mm versus 5.6 ± 1.23 mm ( P < .148), while the internal rotation was significantly less in the reconstructed knees, 7.5° ± 2.96° versus 11.9° ± 3.36° ( P < .05). The values for the coupled movements were used to calculate the length of the radius of curvature, about which the tibia rotates relative to the femur, during the pivot shift. In the control knees, the mean value was 28.9 ± 8.21 mm, while there was extreme variability in the operated knee both before and after surgery. Conclusion: It is possible to reduce both anterior translation and internal rotation, which occur during the pivot-shift test in the ACL-deficient knee, using single-bundle ACL reconstruction, when measured at the time of surgery. However, normal motion is not fully restored.